From Farm to Fork: Evaluating the Socio-Economic and Environmental Impact of Consumer Meat Preferences in Support of Local Agriculture (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Consumer food choices, particularly regarding meat consumption, significantly influence both environmental sustainability and rural economic development. This study examines how consumer preferences for locally sourced versus industrially produced meat impact local agricultural systems, ecological outcomes, and socio-economic conditions. A total of 292 questionnaires were distributed through an online platform. Using a descriptive analysis and Binary Logistic Regression Model, the research explores the drivers of meat purchasing decisions. Results indicate that Malaysian consumers frequently prioritise factors such as price, availability, and brand recognition, even while expressing preference for locally sourced and halal meat. However, barriers such as price sensitivity, consumer awareness, and distribution access limit broader adoption. The study concludes with policy and market recommendations to promote sustainable meat consumption that benefits both local communities and the environment such as addressing price sensitivity, improving consumer awareness, enhancing halal certification, and improving network system and availability of local meat.
Keywords: Local agriculture; consumer behaviour; meat consumption; sustainability; socio-economic impact; environmental awareness